Management of Failed Shoulder Surgery (Springer Berlin Heidelberg, 2018)
In this book, leading European shoulder experts review the current status in the management of failures of surgical treatment of different pathological conditions around the shoulder, such as instability of the glenohumeral joint and the acromioclavicular joint, rotator cuff disease and pathology of the long head of the biceps tendon, and glenohumeral osteoarthritis. The aim is to equip readers with clear guidance on how to manage such failures in everyday practice. There is a particular focus on all aspects of the management response to failure of shoulder arthroplasty. Information is provided on the reasons for failure of the various procedures, and key points on controversial topics are highlighted. Furthermore, case examples are used to present challenging scenarios and their possible solutions. The numerous high-quality illustrations aid comprehension, and readers will also have access to supplementary online videos. The book, published in cooperation with ESSKA, will be invaluable for orthopaedic surgeons and highly relevant for other medical and health practitioners such as sports medicine doctors, physical medicine doctors, and physical therapists.